Instrumentalisierte Verantwortung?: Entstehung und Motive des »Business Case for CSR« im deutschen Diskurs unternehmerischer Verantwortung - Lohmeyer, Nora (transcript, 2017)
The instrumentalisation of business responsibility: this book discursively examines the concept and motives of business responsibility in Germany.